2018
DOI: 10.3324/haematol.2017.182972
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized fibrinogen activates human platelets through glycoprotein VI

Abstract: Glycoprotein VI, a major platelet activation receptor for collagen and fibrin, is considered a particularly promising, safe antithrombotic target. In this study, we show that human glycoprotein VI signals upon platelet adhesion to fibrinogen. Full spreading of human platelets on fibrinogen was abolished in platelets from glycoprotein VI- deficient patients suggesting that fibrinogen activates platelets through glycoprotein VI. While mouse platelets failed to spread on fibrinogen, human-glycoprotein VI-transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 52 publications
6
99
2
Order By: Relevance
“…In sharp contrast, it has been shown that this complex plays a key role in thrombus growth, for example, in platelet‐platelet interactions, by mediating the recruitment of circulating platelets to von Willebrand factor (VWF) exposed at the surface of activated platelets within the thrombus . Moreover, we recently reported that platelet aggregation under flow also involves GPVI, whereas this receptor does not participate in platelet‐platelet interactions under the low shear conditions found in LTA . In addition, the part played by soluble agonists such as thrombin, ADP, or TxA 2 might be overestimated in suspension assays like LTA where they are not washed away by the flow.…”
Section: Platelet Function Testingmentioning
confidence: 95%
See 1 more Smart Citation
“…In sharp contrast, it has been shown that this complex plays a key role in thrombus growth, for example, in platelet‐platelet interactions, by mediating the recruitment of circulating platelets to von Willebrand factor (VWF) exposed at the surface of activated platelets within the thrombus . Moreover, we recently reported that platelet aggregation under flow also involves GPVI, whereas this receptor does not participate in platelet‐platelet interactions under the low shear conditions found in LTA . In addition, the part played by soluble agonists such as thrombin, ADP, or TxA 2 might be overestimated in suspension assays like LTA where they are not washed away by the flow.…”
Section: Platelet Function Testingmentioning
confidence: 95%
“…Washed platelet suspensions are thus ideal for investigations using LTA, flow cytometry, electron microscopy, western blotting of platelet lysates, or radioligand binding, to mention only a few applications …”
Section: Applicationsmentioning
confidence: 99%
“…In one study, the GPVI‐fibrin interaction occurred only with GPVI in dimeric form and could be abrogated by pretreatment with collagen or CRP, implying at least partial overlap of the binding site for these ligands, however, fibrin‐GPVI monomer interactions and separate CRP and fibrin binding sites were proposed in another study . Under certain experimental conditions and in collaboration with αIIbβ3, the fibrin monomer component fibrinogen also can engage GPVI . Understanding how these two GPVI ligands intersect and contribute to GPVI function is important, as selective disruption of one type of GPVI‐ligand interaction, either through competitive inhibition at the ligand‐binding site, or at the level of GPVI dimerization represents an enticing new approach to develop antiplatelet agents with minimal effects on hemostasis.…”
Section: Triggers Of Platelet Receptor Sheddingmentioning
confidence: 99%
“…108 Under certain experimental conditions and in collaboration with αIIbβ3, the fibrin monomer component fibrinogen also can engage GPVI. 33,34 Understanding how these two GPVI ligands intersect and contribute to GPVI function is important, as selective disruption of one type of GPVI-ligand interaction, either through competitive inhibition at the ligand-binding site, or at the level of GPVI dimerization represents an enticing new approach to develop antiplatelet agents with minimal effects on hemostasis.…”
Section: Exposure To Gpvi Ligandsmentioning
confidence: 99%
See 1 more Smart Citation